Prevention of neonatal hypoglycaemia with oral dextrose gel among high-risk neonates born in tertiary care centre - Pandurangan, Uthayashree; Bhosgi, Revanasiddappa (International Journal of Contemporary Pediatrics, 2025)
Background: Neonatal hypoglycemia, a significant cause of neurodevelopmental impairment, affects approximately 25% of neonates, particularly those at high risk, such as preterm, small for gestational age (SGA), large for gestational age (LGA), and infants of diabetic mothers (IDM). These infants may require intravenous dextrose therapy if blood glucose levels do not normalize with feeding alone. This study aimed to assess the effectiveness of oral 40% dextrose gel in preventing hypoglycemia, improving neurodevelopmental outcomes, and reducing hospital admissions and promoting early breastfeeding initiation. Methods: This prospective study included neonates at risk for hypoglycemia, including preterm infants, SGA, LGA, and IDM, delivered at Gulbarga institute of medical sciences over 3 months. Neonates with endocrine disorders or sepsis were excluded. Each neonate in the study received 200 mg/kg (0.5 ml/kg) of oral dextrose gel, administered buccally. Capillary blood glucose levels were monitored every 6 hours for 72 hours. Results: A total of 52 neonates were randomized into two groups: Group A (n=26) received oral dextrose gel, while group B (n=26) did not. In group A, 7.6% developed asymptomatic hypoglycemia, with 3.8% requiring intravenous dextrose. In group B, 26% had asymptomatic hypoglycemia, and 15% required intravenous dextrose. The differences in hypoglycemia incidence and intravenous dextrose use were not statistically significant (p=0.125 and p=0.323, respectively). Similarly, there was no significant difference in hospital stay duration (p=0.574). Conclusions: Oral 40% dextrose gel did not significantly reduce hypoglycemia incidence or intravenous dextrose use compared to breastfeeding alone, nor did it affect the length of hospital stays.